Polizei und Massendaten - Butz, Felix (Nomos Verlagsgesellschaft mbH & Co. KG, 2024)
The ideal of the data-driven police promises security in a world that is perceived as increasingly insecure. Equipped with a growing array of new technologies, the "datafied" police is supposed to enable more effective state social control. This security policy project has set in motion a profound transformation of police information and police social control, which the author examines from a multidisciplinary perspective. He comes to the conclusion that the police information architecture oscillates between overindependence and being overwhelmed. The dissertation develops scenarios as a basis for a proactive design of police social control in the late modern society of the 21st century.